The intersection between toxicology and aging research: A toxic aging coin perspective - Wise Jr, John P. (Frontiers in Aging, 2022)
We are imminently faced with the challenges of an increasingly aging population and longer lifespans due to improved health care. Concomitantly, we are faced with ubiquitous environmental pollution linked with various health effects and age-related diseases which contribute to increased morbidity with age. Geriatric populations are rarely considered in the development of environmental regulations or in toxicology research. Today, life expectancy is often into one’s 80s or beyond, which means multiple decades living as a geriatric individual. Hence, adverse health effects and late-onset diseases might be due to environmental exposures as a geriatric, and we currently have no way of knowing. Considering aging from a different perspective, the term ‘gerontogen’ was coined in 1987 to describe chemicals that accelerate biological aging but has largely been left out of toxicology research. Thus, we are challenged with a two-faced problem that we can describe as a “toxic aging coin”; on one side we consider how age affects the toxic outcome of chemicals, whereas on the other side we consider how chemicals accelerate aging (i.e. how chemicals act as gerontogens). Conveniently, both sides of this coin can be tackled with a single animal study that considers multiple age groups and assesses basic toxicology of the chemical(s) tested and aging-focused endpoints. Here, I introduce the concept of this toxic aging coin and some key considerations for how it applies to toxicology research.